Implementasi Metode Drill dalam Hafalan Surat Pendek Juz 30 Pada Anak Usia Dini - Mutinah Mutinah; Srifariyati Srifariyati; Nursidik Nursidik; Citra Etika (STAI Publisistik Thawalib Jakarta, 2024)
The training method, often referred to by various names such as readiness training method, habituation method, coaching method, and drill, is a technique commonly used by teachers, both inside and outside the classroom. In Tahfidz learning, there is a difference compared to other subjects because the main focus is on the memorization aspect. Memorizing verses of the Qur'an requires precision and caution because errors in memorization can have fatal consequences. Early childhood is considered the golden age for learning as it is the best developmental period for children. This period is crucial for laying the foundations of intelligence, personality, and creativity in individuals. Cognitively, children at this age have high absorption potential. Therefore, it is the right time to start the process of memorizing short verses. In this study, the approach used is qualitative method with field research aiming to obtain descriptive or narrative data about background, social groups, individuals, and community institutions. The research findings indicate that Tahfidz learning (memorization of short verses from Juz 30) is conducted with enthusiasm, activity, creativity, and cheerfulness, and the children are able to follow the learning process well.